Penciptaan Busana Ready To Wear Deluxe dengan Sumber Ide Lautan Pasir Gunung Bromo - Sayidatul Istighfarini; Inty Nahari; Deny Arifiana; Mita Yuniati (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This research focuses on the creation of ready-to-wear deluxe fashion inspired by the sand sea of Mount Bromo. The objectives of this research are to describe the creation process of deluxe ready to wear fashion inspired by the sea of sand of Mount Bromo, to produce deluxe ready to wear fashion inspired by the sea of sand of Mount Bromo, and to publish the result of creation of deluxe ready to wear fashion inspired by the sea of sand of Mount Bromo, . The type of research used in this study is artistic research, emlpying a practice-led research method, which consists of four stages: pre-design, design, realization, and presentation. The results of this research are three sets of ready-to-wear deluxe garments categorized as special occasion stage wear, which represent the visual characteristics of Mount Bromo's sand sea through material selection, color, silhouette, and fabric manipulation techniques. The work was showcased at the “34th Fashion Show UNESA: Bhumibrama,” as a form of appreciation for Indonesia’s natural heritage, presented in a modern fashion concept. The conclusion of this research reveals that nature exploration, particularly the visual elements of the sand sea of Mount Bromo, can serve as a strong source of inspiration for fashion design. This work demonstrates that Indonesia’s natural heritage can be transformed into fashion concepts with both aesthetic value and high commercial potential.